Historical and theoretical aspects of the development of democracy in society - Пильгун, Наталія Василівна; Яківчук, Жанна Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article defines democracy in our country and other legal countries with rich history. It will tell us about human rights, liberties, principles and different theories of democracy. Also this acticle dedicates to disclosure many concepts, which are basic for understanding functions and problems of Ukraine. Formulation of the problem. The problem of the chosen theme is very actual and painful in our society. And at first we can watch it in Ukraine. And it is not surprising, because the young Ukrainian country still stands in the way of legal principles. The authorities are reluctant to take up the development of democracy in our country. But before the next new elections politics again start talking about democracy, thus increasing your ranking in the election. But words, unfortunately, are only words, written on paper. After the election everything is fading. This is one of the biggest mistake of Ukrainian democracy. So the younger generation should know all of the problems very well in order to effectively solve them. It should be done, considering the different principles of democracy, understanding the difference between her views and skillfully combine them to build a democratic society and a democratic state. Presenting main material. Everybody knows that democracy is not a government; it is a way of thinking, a responsibility. In the democracy there is no corruption in power because it is a transparent system: the governing doctrine states that citizens have the right to access the documents and proceedings of the government, which allows for effective public oversight. Like a sculptor, democracy grows with its work and appreciates its art. The rule of law and the protection of human rights are necessary for a democracy to function/ to exist in reality. This is because in a democracy the people are the sovereign and hence govern themselves. For this democratic governance, the citizens must agree in democratic processes on the rules and law. Without democracy, society suffers. In dictatorships there is no celebration of thought or creativity. A country cannot thrive if others’ opinions are not appreciated. With only one opinion adhered to, the country will be at a standstill. That is why our country must concentrate all its powers to build new democratic state in which people’s rights would be in the first place, in which principles of the democracy will be implemented in real life and the country will be done all its functions. Conclusions. We must know all theories of democracy, all its functions and basic principles in order to make our life better. Without history of democracy people can’t understand problems of reality or provide future.